(untitled) (Harmoni, 2012)
Religious institutions have given much contribution to the society through fund management and social asset. One of the religious institutions is the Church (PAROKI) cathedral in Jakarta. Through the research with a qualitative approach, it is revealed this institution has implemented a system and mechanism for social religious funding management effectively and efficiently, with healthy, transparent and accountable management system. The distribution of collected funds, for the social activities carried out by the church, was done through the Social Section of the Paroki (SSP) or Social-Economic Development (PSE) in the form of charitable/ consumptive aid, and the empowerment of education institutions under the Vincent association. The empowerment through the educational programs are considered successful, because it accomplishes the indicators of empowerment, while another program is merely a stimulant because it was charitable / consumptive.